Identificacion del consumo de alcohol, tabaco y otras sustancias psicoactivas a los estudiantes de odontología de la Universidad Antonio Nariño sede Armenia 2021. (2021)
The students of the Faculty of Dentistry of the Antonio Nariño University, Armenia headquarters, like all higher education institutions, have an increase in the use of alcohol, tobacco and / or other psychoactive substances and this is due to different social situations, legal and personal that generate vulnerability especially in the youngest as it will be seen later. This study is descriptive, observational, cross-sectional, the structured survey was applied to 106 students of the II - X semester of the Faculty of Dentistry of the Antonio Nariño University (2021), using the instrument, approved by the WHO ("Test detection of alcohol, tobacco and substances "" ASSIST ", 2011)and was modified for this study, inclusion and exclusion criteria were used to obtain reliable results.